Budidaya Ikan Cupang Pemutus Mata Rantai Penyebab Penyakit Demam Berdarah Dengue di Lingkungan Sekolah Menengah Atas Negeri 2 Kota Tarakan - Satriani, Gloria Ika; Amien, Muhammad; Azis, Azis; Iromo, Heppi; Sumarni, Titin; Wulandari, Irene Caya (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Dengue hemorrhagic fever often appears in the rainy season and is more common in tropical areas. Dengue fever is transmitted through mosquito bites, such as Aedes aegypti or Aedes albopictus females, who have the virus transmitted into the human body. This mosquito bites humans in the morning and afternoon. Natural factors and human behavior can cause this virus to appear. Mosquito A.aegypti could live and reproduce in crowded and unclean places, especially in standing water. One way to prevent dengue fever is to cover and drain areas of standing water. Another way to do this is to keep fish that eat larvae in water reservoirs. Using insecticides to stop the chain of mosquito-spread during the larval stage is one method that is often used to control A.aegypti; the extermination of mosquito larvae is more effective than adult mosquitoes. Betta, as a predator of mosquito larvae A.aegypti, can break the chain of dengue fever naturally and effectively. This community service activity (PKM) involves outreach within the SMA Negeri 2 Tarakan City environment.